Elevated arterial blood pressure after superior cavo-pulmonary anastomosis is associated with elevated pulmonary artery pressure and cerebrovascular dysautoregulation. (September 2018) - Cabrera, Antonio; Kibler, Kathleen; Blaine Easley, R; Goldsworthy, Michelle; Shekerdemian, Lara; Andropoulos, Dean; Heinle, Jeffrey; Gottlieb, Erin; Vu, Eric; Brady, Ken
Abstract Background Elevated arterial blood pressure (ABP) is common after superior bidirectional cavopulmonary anastomosis (BCPA). The effects of elevated ABP after BCPA on cerebrovascular hemodynamics are unknown. We sought to determine the relationship between elevated ABP and cerebrovascular autoregulation after BCPA. Methods Prospective, observational study on infants with single-ventricle physiology after BCPA surgery. Continuous recordings of mean ABP, mean cavopulmonary artery pressure (PAP), near-infrared spectroscopy measures of cerebral oximetry (regional cerebral oxygen saturation (rSO2 )), and relative cerebral blood volume index were obtained from admission to extubation. Autoregulation was measured as hemoglobin volume index (HVx). Physiologic variables, including the HVx, were tested for variance across ABP. Results Sixteen subjects were included in the study. Elevated ABP post-BCPA was associated with both, elevated PAP (P <0.0001) and positive HVx (dysautoregulation;P <0.0001). No association was observed between ABP and alterations in rSO2 . Using piecewise regression, the relationship of PAP to ABP demonstrated a breakpoint at 68 mm Hg (interquartile range (IQR) 62–70 mm Hg). Curve fit of HVx as a function of ABP identified optimal ABP supporting robust autoregulation at a median ABP of 55 mm Hg (IQR 51–64 mm Hg). Conclusions Elevated ABP post-BCPA is associated with cerebrovascular dysautoregulation, and elevated PAP. The effects, of prolonged dysautoregulation within this population, require further study.